Preparation and Characterization of Chitosan-HarpinXooc Nanoparticles - Zhan1, Jiang; Wu1, Huijun; Yang1, Yang; Wang1, Shuai; Zhan2, Xiaojuan; Gao1, Xuewen (Asian Journal of Chemistry, 2013)
The chitosan-HarpinXooc nanoparticles were prepared by the electrostatic interaction of chitosan (CS) with HarpinXooc and the ionic gelation of chitosan with tripolyphosphate (TPP). The particle sizes (197-653 nm) and zeta potential (29-15 mV) of the nanoparticles, which were changed with the preparing conditions such as the pH value (4.8-6.8), CS/TPP mass ratio (20:1-6:1) and HarpinXooc concentration (50-400 μg/mL), were determined respectively by dynamic light scattering and zeta potential analyzer. These preparing conditions were also examined systematically for their effects on the particles physicochemical properties such as encapsulation efficiency, loading capacity and release behavior at 26 ± 2 °C. The morphology and microstructure of the chitosan-tripolyphosphate nanoparticles were revealed by the transmission electron microscope analysis. This study demonstrated that systematic design and modulation of the chitosan-HarpinXooc nanoparticles could be readily achieved with the right control of processing conditions and would provide a sound basis to further exploration of HarpinXooc loaded nanoparticles.